ASSESSMENT OF THE EXIT OF ENTREPRENEURS FROM THEIR BUSINESS IN 2020 IN THE CONTEXT OF PANDEMIC: DIFFERENT COUNTRIES DATA - Pinkovetskaia, Iuliia (Formação (Online), 2022)
Due to the significant impact of the consequences of the Covid-19 pandemic on the exit of entrepreneurs from their businesses, it seems relevant to study the reasons for the termination of entrepreneurs’ activities in various countries. The purpose of the study is to assess the current level of exit of entrepreneurs from their businesses in national economies in 2020. The opinions of entrepreneurs who left businesses about the reasons for this were considered. The initial data were the results of a survey of entrepreneurs in 39 countries during the work on the project "Global Monitoring of Entrepreneurship". We evaluated four indicators that characterize the positive and negative reasons for the termination of their activities by entrepreneurs. It is proved that the majority (56.3%) of all entrepreneurs who stopped their activities did so for negative reasons, but not related to the Covid-19 pandemic. It is proved that more than a quarter (almost 28%) of all entrepreneurs who left their businesses were forced to do so due to the negative consequences of the pandemic. It is shown that only one in six of these entrepreneurs had positive reasons for leaving their businesses in 2020. Since the data describing the exit of entrepreneurs from their businesses were considered, there were restrictions in 39 countries due to the lack of information for the rest of the countries. Further research may be related to the assessment of the consequences of the pandemic in 2021.